PERANAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN SISTEM PEMASARAN - IRNAWATI IRNAWATI (LPPM, 2015)
In a company, one of the things associated with the continuity of the company is how to market products owned. The company marketing of real estate agent to looking for a match between the client (the seller) and the client (the buyer) until there is be agreement. As serviices company, marketing associate is the most instrumental in marketing the property, therefore the performance of marketing associate is expected by company. In this writing illustrates how the environment, commitment, technology, and performance marketing associate interplay. Research methodology using questionare of 50 respondents who are members of the marketing associate of three real estate agencies. Analysis of the model used to test the hypothesis, using proportionate, random sampling, whereas analysis techniques using path analysis. The results showed that, partially, environmentally significant direct effect on the databases must address satisfying marketing associate, with a contribution of 0.701. The Other results obtained are no direct influence on the performance of information technology marketing associate, while significant commitment directly influence the performance of the marketing associate with a contribution of 0.224. For environment, commitment, technology significantly affect the performance of marketling associate with kontributions by 57%. Keywords: Utilization of Information Technology, environment, technology, commitment, performance